This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
To solve this, we must know the first principle of differentiation according to which we have h → 0 lim ( h f ( x + h ) − f ( x ) ) = f ′ ( x ) . Now, we have in this question that f ( x ) is a function differentiable at x = 1 with f ′ ( 1 ) = 5 1 . So ----
x → 1 lim ( f ( x ) − f ( 1 ) x 3 − 1 )
= x → 1 lim ( x − 1 f ( x ) − f ( 1 ) x − 1 x 3 − 1 ) [dividing both numerator and denominator by ( x − 1 ) ]
= x − 1 → 0 lim ( x − 1 f ( x ) − f ( 1 ) ) x → 1 lim ( x − 1 x 3 − 1 ) [since x → 1 ⟹ x − 1 → 0 ]
= x − 1 → 0 lim ( x − 1 f ( 1 + ( x − 1 ) ) − f ( 1 ) ) x → 1 lim ( ( x − 1 ) ( x − 1 ) ( x 2 + x + 1 ) ) [since a 3 − b 3 = ( a − b ) ( a 2 + a b + b 2 ) ]
= f ′ ( 1 ) x → 1 lim ( x 2 + x + 1 ) [from first principle taking x = 1 , h = ( x − 1 ) ]
= 5 1 1 2 + 1 + 1 = 5 1 1 + 1 + 1 = 5 1 3 = 3 × 5 = 1 5